Aerosol synthesis of germanium nanoparticles supported by external seeding: Theoretical and experimental analysis - Wergen, Lukas; Domaschke, Maximilian; Herre, Patrick; Wu, Mingjian; Spiecker, Erdmann; Peukert, Wolfgang (Journal of Aerosol Science, 2019)

A model for the particle mass yield in the aerosol synthesis of ultrafine monometallic nanoparticles by spark ablation - Domaschke, Maximilian; Schmidt, Melanie; Peukert, Wolfgang (Journal of Aerosol Science, 2018)
Keywords: Nanoparticles; Scanning mobility particle sizer; Aerosol synthesis; Dimensional analysis; Spark ablation

A model for the particle mass yield in the aerosol synthesis of ultrafine monometallic nanoparticles by spark ablation - Domaschke, Maximilian; Schmidt, Melanie; Peukert, Wolfgang (Journal of Aerosol Science, 2018)
Keywords: Nanoparticles; Scanning mobility particle sizer; Aerosol synthesis; Dimensional analysis; Spark ablation

Analysis of ultrafine metal oxide particles in aerosols using mobility-resolved time-of-flight mass spectrometry - Domaschke, Maximilian; Lübbert, Christian; Peukert, Wolfgang (Journal of Aerosol Science, 2019)
In this work we present a powerful method to gain insight into the formation of inorganic nanoparticles from the gas phase by combining a high-resolution differential mobility analyzer with a time-of-flight mass spectrometer. Exemplary particles are generated by glowing-wire evaporation from tungsten, tantalum, rhenium, niobium and molybdenum and transferred via a new custom-made interface to the mobility classifier that is directly attached to the mass spectrometer. With only minor fragmentation occurring, clusters that represent early stages of particle formation from the gas phase can be detected. Regardless of the inert experimental conditions, only oxides were found for all tested precursor metals. Comparing the recorded mass-mobility data with theoretical predictions from a modified Mason-Schamp equation shows that produced materials possess densities smaller than those of the respective bulk materials. The maximum observed particle sizes were about 2 nm.
CRIS-Team Scopus Importer:2019-08-27
Keywords: Differential mobility analyzer; Glowing-wire evaporation; Multidimensional characterization; Nanoparticles; Time-of-flight mass spectrometry

Magnéli Phases Doped with Pt for Photocatalytic Hydrogen Evolution - Wierzbicka, Ewa; Domaschke, Maximilian; Denisov, Nikita; Fehn, Dominik; Hwang, Imgon; Kaufmann, Marlena; Kunstmann, Babette; Schmidt, Jochen; Meyer, Karsten; Peukert, Wolfgang; Schmuki, Patrik (ACS Applied Energy Materials, 2019)
Defined TiOx suboxides (Magnéli phases) have rarely been investigated in photocatalysis. In the current work we describe a one-step synthesis of Magnéli-containing mixed phase nanoparticles that carry directly integrated minute amounts with a few hundred ppm of Pt. Nanoparticles can act as highly effective photocatalysts, e.g., mixed phase particles of 32% anatase, 11% rutile, and 57% Magnéli phases loaded with 290 ppm of Pt which provide a 50-100 times higher H2 evolution than plain anatase loaded with a similar amount of Pt. This high photocatalytic efficiency is ascribed to a multijunction of various Magnéli titania species and Pt.
CRIS-Team Scopus Importer:2019-12-20
Keywords: H; Magnéli phase; multiphase titania; photocatalysis; Pt cocatalyst

Magneli-Phases in Anatase Strongly Promote Cocatalyst-Free Photocatalytic Hydrogen Evolution - Domaschke, Maximilian; Zhou, Xuemei; Wergen, Lukas; Romeis, Stefan; Miehlich, Matthias; Meyer, Karsten; Peukert, Wolfgang; Schmuki, Patrik (ACS Catalysis, 2019)
Magneli phases of titanium dioxide (such as Ti4O7, Ti5O9, etc.) provide electronic properties, namely, a stable metallic behavior at room temperature. In this manuscript, we demonstrate that nanoscopic Magneli phases, formed intrinsically in anatase during a thermal aerosol synthesis, can enable significant photocatalytic H-2 generation-this without the use of any extrinsic cocatalyst in anatase. Under optimized conditions, mixed-phase particles of 30% anatase, 25% Ti4O7, and 20% Ti5O9 are obtained that can provide, under solar light, direct photocatalytic H-2 evolution at a rate of 145 mu mol h(-1) g(-1). These anatase particles contain 5-10 nm size intergrown phases of Ti4O7 and Ti5O9. Key is the metallic band of Ti4O7 that induces a particle internal charge separation and transfer cascade with suitable energetics and favorable dimensions that are highly effective for H-2 generation.
CRIS-Team WoS Importer:2019-04-23

Single-step aerosol synthesis of oxygen-deficient blue titania - Domaschke, Maximilian; Strunz, Lea; Peukert, Wolfgang (Chemical Engineering Science, 2019)
We present a novel approach for the single-step, continuous aerosol synthesis of blue, oxygen-deficient titania in a hot-wall reactor operated under reducing conditions by adding hydrogen. The precursor titanium(IV) tetraisopropoxide is evaporated in a bubbler and consecutively carried into the reactor by a nitrogen stream where it undergoes thermal decomposition. According to X-ray diffraction analysis, several reduced titania states, among them the Magneli phases Ti4O7 and Ti5O9, are formed via the intermediates anatase and rutile. By slight modifications in the reactor setup both nanoparticles in the size range from 20 to 50 nm with high surface area and well-defined spherical submicron particles of 100 to 160 nm diameter can be produced. In particular, crystallographically phase-pure Ti4O7 is formed at high reactor temperatures. The presented synthesis process is scalable and poses an attractive alternative for the multi-step synthesis of oxygen deficient titania nanoparticles that is currently done via batch-wise annealing. Such nanoparticles are attractive material in the field of photocatalysis. They can be used for both water splitting to produce hydrogen and the decomposition of organic pollutants. (C) 2019 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2019-07-02